Evaluasi dan Perbaikan User Experience pada Situs Web Sistem Informasi Mahasiswa Online (SIMON) Universitas Warmadewa menggunakan User Experience Questionnaire (UEQ) dan Human Centered Design (HCD) - Anak Agung Gede Krisna Eka Putra; Hanifah Muslimah Az-Zahra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Online Student Information System (SIMON) is an academic information system owned by Warmadewa University which is used to support the academic administration process of its students. Based on the results of discussions with one of the developers of the Warmadewa University information system, it was found that the SIMON itself has never been evaluated in terms of user experience. The information obtained through unstructured interviews that the author has conducted with seven students of Warmadewa University, also shows that the interface of the SIMON website interface is rather inconsistent, seems outdated and unattractive. This is certainly not desirable because it can have an impact on the experience and productivity of students as users and of course, not in accordance with the vision and mission of Warmadewa University. Therefore, an evaluation was carried out to determine the level of user experience and problems contained in SIMON Warmadewa with the User Experience Questionnaire (UEQ) and also Usability Testing to find out the level of user experience, usability and existing problems. From the findings of the problems that have been evaluated, improvements were made through the design of an interface design that has a better user experience using a Human Centered Design (HCD). The results of the design were then evaluated using UEQ, where it was found that the usability and user experience values showed positive and better values compared to the current SIMON Warmadewa interface display.